Impact of Supply Chain Management Towards Improved Quality of Libraries Services - Nabil Abdullah komosany; Hassan Abdullah Alqarni (International Journal of Computers and Informatics, 2024)
This study about the impact of supply chains in libraries, one of the main objectives of the study to know the framework of supply chains, and to know the applications of supply chains in libraries, the study used descriptive approach. Researchers mention some examples of supply chain in libraries, and some libraries experiences applied this concept, finally researchers reviewed the most important challenges faced libraries while applied supply chain.